Periodization of strength training for sports - Bompa, Tudor O.; Buzzichelli, Carlo 1973- (Champaign, IL Human Kinetics, 2022)
"Periodization of Strength Training for Sports demonstrates how to use periodized workouts to peak at optimal times by manipulating strength training variables through six training phases-anatomical adaptation, hypertrophy, maximum strength, conversion to specific strength, maintenance, and tapering"--
Part 1. Foundations of Strength Training -- Strength, power, and muscular endurance in sports -- Neuromuscular response to strength training -- Laws and principles of strength training for sports -- Part 2. Planning, Periodization, and Program Design -- Manipulations of training variables -- The microcycle short term plan -- The annual plan -- Long term planning for team sports -- Part 3. Periodization of Strength -- Anatomical adaptation -- Hypertrophy training -- Maximum strength -- Conversion to specific strength -- Maintenance, cessation, and compensation -- Peaking for maximum performance.
Third edition published: Champaign : Human Kinetics, [2015], under title Periodization training for sports.
Includes bibliographical references and index.
Keywords: Periodization training; Weight training